The potential role of cuproptosis-related genes for therapy and immunoregulation in pan-cancer. - Jianpeng Zhou; Chuanlei Wang; Yao Zhi; Jia Li (PLoS ONE)
The primary drawbacks of current cancer therapies are lower selectivity for cancer cells, more side effects, and obscure resistance mechanisms. Novel approaches to overcome these drawbacks comprise the utilization of ionophores and metalliferous chelators to change the concentration of trace metal elements in cancer cells. As the concept of cuproptosis emerged, it might be a novel strategy to enhance the curative effects for resistant cancer cells potentially. FDX1, LIAS, LIPT1, DLD, DLAT, PDHA1, PDHB, and SLC31A1 are the major regulators of cuproptosis. However, the expression landscape and clinical roles of these regulators remain to be addressed. This study explored the expression pattern and clinical role of these cuproptosis-related genes in pan-cancer by evaluating the association of tumor mutation burden (TMB), immune-related scores, cells in tumor microenvironment, and drug sensibility. The results displayed that the expressions of cuproptosis-related genes were significantly different in various cancer types, all cuproptosis-related gene upregulates significantly in LAML, ALL, PAAD, GBM, GBMLGG, LGG, and all significantly downregulated in cancers KIPP, WT, KIPAN, KIRC. Furthermore, the higher the level of cuproptosis-related genes expressed, the higher the survival in patients suffering from KIRC, and KIPAN increased. In addition, the expression of cuproptosis-related genes was negatively associated with immune-related scores, while SLC31A1 had a positive association with StromalScore, ImmuneScore, and EstimateScore in LAML. Importantly, the expression of cuproptosis-related genes was positively correlated with common lymphoid progenitor (CLP) cells and Th2 cells, but negatively associated with NKT cells or Th1 cells. These findings suggest that cuproptosis-related genes are dysregulated across cancer types, hold prognostic value, and may be involved in modulating the tumor immune microenvironment.